The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1136/jme.24.2.106
|View full text |Cite
|
Sign up to set email alerts
|

The right to information for the terminally ill patient.

Abstract: Objectives-To analyse the attitudes of medical personnel towards terminally ill patients and their right to be fully informed. Design-Self-administered questionnaire composed of 56 closed questions. Setting-Three general hospitals and eleven health centres in Granada (Spain). The sample comprised 168 doctors and 207 nurses. Results-A high percentage of medical personnel (24. 1%) do not think that informing the terminally ill would help them face their illness with greater serenity. Eighty-four per cent think t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…Percentages of healthy people who would like to die at home were generally higher than those who actually die at home [200] , [201] , [202] , [203] , [204] , [205] nevertheless a recent survey showed that half of the population has preferences for specific care settings or hospitals for terminal patients [202] . There was greater consensus among healthcare professionals than among the general public that the home is the ideal place of death [206] , [207] , [208] , [209] .…”
Section: Resultsmentioning
confidence: 99%
“…Percentages of healthy people who would like to die at home were generally higher than those who actually die at home [200] , [201] , [202] , [203] , [204] , [205] nevertheless a recent survey showed that half of the population has preferences for specific care settings or hospitals for terminal patients [202] . There was greater consensus among healthcare professionals than among the general public that the home is the ideal place of death [206] , [207] , [208] , [209] .…”
Section: Resultsmentioning
confidence: 99%
“…Osuna et al also reported that Spanish nurses believed they were more capable of working with terminally ill patients and showed less distress than did physicians. 24 Many nurses thought that treatment continues too long, a finding that is probably owing to the fact that nurses spend much time with patients and hopeless care is therefore more visible to them. Sjökvist et al also reported that a substantial minority of nurses disagreed with physicians' decisions on life-supporting treatments.…”
Section: Nurses' Rolesmentioning
confidence: 99%
“…Percentages of healthy people who would like to die at home were generally higher than those who actually die at home [200,201,202,203,204,205] nevertheless a recent survey showed that half of the population has preferences for specific care settings or hospitals for terminal patients [202]. There was greater consensus among healthcare professionals than among the general public that the home is the ideal place of death [206,207,208,209].…”
Section: Spainmentioning
confidence: 99%
“…International comparisons described southern European countries as partial and non-disclosure countries [221,222,223] and Spanish awareness studies suggested that this trend persisted over time [194,204,218,224,225,226,227]. On the other hand, studies with healthy populations show that preferences are evolving towards open disclosure [201,202,203,204,207,228]. Intermediate positions were also found; the majority of doctors stated that they would inform the patient only in certain circumstances or if requested by the patient [206,207,208,209,228,229,230,231,232].…”
Section: Spainmentioning
confidence: 99%
See 1 more Smart Citation